The Psychological Challenges of Emergency Medical Service Providers During Disasters: A Mini-Review February 2022 - Alghamdi, Abdullah Abdulaziz (Frontiers in Psychiatry, 2022)
Provision of Emergency Medical Services EMS is an inherently stressful job. Depression, anxiety, and Post Traumatic Stress Disorder PTSD are common psychological challenges affecting EMS providers. As disasters increase worldwide, the need for EMS increases because it is an essential part of any disaster management system. Studies showed that EMS providers had experienced psychological challenges due to disaster response without receiving the needed psychological support. There is a scarcity of research focusing on EMS providers’ psychological challenges in disaster times specially in the eastern world. This review highlights the psychological challenges faced by EMS providers in disaster times and discusses the amount of mental healthcare they receive. By emphasizing the need for mental health support, more research can be done to view EMS providers’ perspective on mental health needs before, during and after disasters, and EMS policymakers can found programs to meet EMS providers’ mental health needs, which might reflect positively on EMS and disaster managements systems.